Autumn leaf color brightness of Japanese alpine vegetation is projected to decrease under future climate change - Dai Koide; Reiko Ide; Hiroyuki Oguma; Keisuke Suzuki; Haruka Ohashi; Yuji Kominami (Scientific Reports)
Abstract Autumn leaf coloring is an essential cultural ecosystem service, but mechanisms of color brightness have scarcely been focused on, even though the autumn color crisis (leaf fall without coloring) has been reported in Japanese alpine shrubs. To approach the mechanisms, we analyzed the relationship between brightness and environmental conditions and projected possible future changes. Autumn color brightness was measured by repeated camera observations at three Japanese alpine sites. Environmental factors were analyzed using linear mixed model comparisons. Results showed earlier green-up timing was related to a duller autumn leaf color, possibly because a prolonged leaf period creates older leaves and reduces physiological vitality in autumn, affecting anthocyanin biosynthesis. Green-up timing based on snowmelt day and degree-day-based prediction of snowmelt day predicted earlier snowmelt and green-up in the future, with decreases in autumn color brightness. The amount of color reduction varied among climate models and scenarios, from a decline of several percent under MRI-CGCM3 RCP 2.6 to around 15% under MIROC5 RCP8.5 by the end of this century. Projected reductions in autumn color brightness could have an economic impact on tourism, and it could also be linked to modifications in material cycles and the ecosystem’s productivity.